Soil Organic Carbon Increases in Semi-Arid Regions while it Decreases in Humid Regions Due to Woody-Plant Encroachment of Grasslands in South Africa. Issue 1 (December 2018) - Mureva, Admore; Ward, David; Pillay, Tiffany; Chivenge, Pauline; Cramer, Michael
Abstract Grasslands and savannas are experiencing intensive land-cover change due to woody plant encroachment. This change in land cover is thought to alter soil carbon (C) and nitrogen (N) storage in these ecosystems. Some studies have reported a negative correlation between soil C and N and mean annual precipitation while others have indicated that there is no relationship with mean annual precipitation. We quantified the changes in C and N pools and δ13 C and δ15 N values to a depth of 1 m in pairs of encroached and adjacent open grassland sites along a precipitation gradient from 300 mm to 1500 mm per annum in South Africa. Our study showed a negative correlation between changes in soil organic C stocks in the 0–100 cm soil layer and mean annual precipitation (MAP). The most humid site (1500 mm MAP) had less C in shrub-encroached sites while the drier sites (300–350 mm MAP) had more C than their paired open grasslands. This study generally showed soil organic C gains in low precipitation areas, with a threshold value between 750 mm and 900 mm. Our threshold value was higher than that found in North America, suggesting that one cannot extrapolate across continents.